Sustainable Land Management Sourcebook - World Bank (Washington, DC, 2012)
This sourcebook is intended to be a ready reference for practitioners (including World Bank stakeholders, clients in borrowing countries, and World Bank project leaders) seeking state-of-the-art information about good land management approaches, innovations for investments, and close monitoring for potential scaling up. This sourcebook is divided into three parts: the first part identifies the need and scope for sustainable land management (SLM) and food production in relation to cross-sector issues such as freshwater and forest resources, regional climate and air quality, and interactions with existing and emerging infectious diseases. It introduces the concept of production landscapes and analysis of trade-offs and establishes a framework for linking indicators that provide a measure of the outcomes of SLM. It then categorizes the diversity of land management (that is, farming) systems globally and the strategies for improving household livelihoods in each type of system. For the farming system types, a set of SLM principles and common but important issues for future investments are identified. The second part of the sourcebook focuses on three major farming system types and presents a range of investment notes and innovative activity profiles. The third part provides users of the source book with easy-to access, web-based resources relevant for land and natural resource managers. The resources are available in the public domain, and readers can access the web sites of various international and national agencies.